Characterization and Beneficiation of Fanibi Laterite for Nickel Metal Recovery Using Froth Flotation Method - Abiola, Tolulope Joseph; Alabi, Oladunni Oyelola; Oloruntoba, Daniel Toyin; Gbadamosi, Yemisi (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
This study investigates the characterization of Fanibi Laterite and the efficiency of froth flotation to beneficiate nickel from its host rock sourced in Akure, Ondo State, Nigeria. A sample of the laterite was obtained and characterized by the use of an X-ray fluorescence Spectrometer (XRFS), X-ray diffractometer (XRD), and Scanning electron microscope with Energy dispersive spectroscope (SEM/EDS). The ore was comminuted to its liberation size of -125 + 90 µm. The froth flotation process was done using Sodium hydroxide and Hydrogen tetraoxosulphate (VI) acid as hydrogen potential (pH) modifier within the range of 4,5,7,9 and 10. However, other reagents are sodium oleate as the collector, potassium dichromate as the depressant, and oleic acid as the frother. The froth and depressed obtained were dewatered and characterized using XRFS. The result revealed that the ore contained 35.65% Si, 8.24% Al, 10.87% Fe, and 0.07% Nickel. It also included some other associated minerals such as Zn, Mg, Ti, Co, and Mo in trace form of less than 1 %. XRD analysis reveals nickel as nickel iodate. The result reveals nickel assays of 0.14, 0.20, 0.15, 0.25, and 0.12%, while their recoveries are 70.82, 67.80, 86.70, 98.04, and 86.98%, respectively. The optimum nickel recovery of 98.04% was attained at a pH of nine (9). It was concluded that froth flotation could successfully beneficiate Fanibi laterite ore for nickel. At the same time, other minerals such as Titanium, Molybdenum, Tin, and Tungsten were present to be extracted for Metallurgical applications.